Information Processing Behaviour of Dairy Farmers in Adoption of Animal Husbandry Practices (Indian Journal of Extension Education, 2009)
The study was conducted in Jind district of Haryana as it has the highest concentration of cattle and buffalo population. A multistage random sampling technique was followed to select 240 dairy farmers from eight villages of the district. Most of the dairy farmers evaluated the worthiness of innovation the worthiness of innovation by considering its profitability (87.92%) and discussing with progressive farmers (77.50%) before adopting innovation, Significant proportion of the dairy farmers retained the information by practicing in daily life (93.33%) followed by informing family members (76.67%) and memorizing (64.17%). The correlation coefficient revealed that socio- economic status, herd size, annual income, extension contact, mass media exposure, risk orientation and cosmopoliteness-localiteness had positive and significant relationship with the information processing behaviour, whereas age of the respondents had negative and significant relationship with the information processing behaviour, The R² value revealed that all the thirteen independent variables fitted in the regression equation had explained about 46 per cent variation towards information processing behaviour.